2021
DOI: 10.1038/s41598-021-00234-5
|View full text |Cite
|
Sign up to set email alerts
|

Sociability strongly affects the behavioural responses of wild guanacos to drones

Abstract: Drones are being increasingly used in research and recreation but without an adequate assessment of their potential impacts on wildlife. Particularly, the effect of sociability on behavioural responses to drone-associated disturbance remains largely unknown. Using an ungulate with complex social behaviour, we (1) assessed how social aggregation and offspring presence, along with flight plan characteristics, influence the probability of behavioural reaction and the flight distance of wild guanacos (Lama guanico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…For example, Przewalski's Horses reacted to drones at different altitudes eliciting escape behavior when flights are below 20 m above ground level [40]. Another study in Argentina showed that guanacos elicited escape behavior in response to drones and the escape distance decreases with the size of the group, with the highest probability of reaction at 60 m AGL [41]. In the African savanna, elephants, giraffes, wildebeests, zebras, impalas, lechwes, and tsessebes showed escape behavior to drones at altitudes between 20 and 60 m AGL [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Przewalski's Horses reacted to drones at different altitudes eliciting escape behavior when flights are below 20 m above ground level [40]. Another study in Argentina showed that guanacos elicited escape behavior in response to drones and the escape distance decreases with the size of the group, with the highest probability of reaction at 60 m AGL [41]. In the African savanna, elephants, giraffes, wildebeests, zebras, impalas, lechwes, and tsessebes showed escape behavior to drones at altitudes between 20 and 60 m AGL [37].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research on behavioral responses of wildlife to drones has been focused on birds [20,22,25,28,29] and marine mammals [1,[30][31][32][33][34][35][36], with less attention to large terrestrial mammals, especially in North America [37]. For instance, behavioral responses have been studied in black bears (Ursus americanus) in North America [38], elephants (Loxodonta africana), giraffes (Giraffa camelopardalis), wildebeests (Connochaetes taurinus), zebras (Equus quagga), impalas (Aepyceros melampus), lechwes (Kobus leche), and tsessebes (Damaliscus lunatus) in African savannas [37], kangaroos (Macropus giganteus) in Australia [39], captive Przewalski's Horses (Equus ferus przewalskii) in China [40], and guanacos (Lama guanicoe) in Argentina [41]. All these studies have detected that drone flights trigger behavioral responses, such as an increase in antipredator behaviors, for example, vigilance and escape behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Samuel and Pollock 1981;Melville et al 2008;Tracey et al 2008), it is possible that flight responses to human disturbance are greater in larger groups (Stankowich 2008). Unmanned aerial vehicles (UAVs) cause greater flight distances in larger groups of guanacos (Lama guanicoe) than in small groups or solitary animals (Schroeder and Panebianco 2021). Other solitary larger herbivores, including ungulates such as the Japanese serow (Capricornis crispus), might be less likely to flush great distances in response to human disturbance, particularly once cover is reached (Takada et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lower flight altitudes or decreasing distance between the drone and the surveyed animals are almost universally associated with disturbance (Bennitt et al, 2019; Fettermann et al, 2019; Headland et al, 2021; McEvoy et al, 2016; Ramos et al, 2018; Rümmler et al, 2021; Schroeder & Panebianco, 2021; Weimerskirch et al, 2018; Weston et al, 2020). While there are exceptions, they appear to be the best general predictors for disturbance and guidelines for the use of drones recommend to always use the highest possible altitude (Duporge et al, 2021; Mulero‐Pázmány et al, 2017).…”
Section: Disturbance and Anti‐predator Behaviourmentioning
confidence: 99%
“…Inter‐individual differences were found to be associated with age categories and the breeding status of individuals (Brisson‐Curadeau et al, 2017; Pomeroy et al, 2015; Weimerskirch et al, 2018). Future research should consider social and demographic factors to evaluate how these aspects of group composition affect group‐level trends during anti‐predator behaviour (Schroeder & Panebianco, 2021; Torney et al, 2018).…”
Section: Disturbance and Anti‐predator Behaviourmentioning
confidence: 99%